New Insights on Long-Term Hepatitis B Virus Responses in HIV–Hepatitis B virus Co-infected Patients: Implications for Antiretroviral Management in Hepatitis B virus-Endemic Settings. (1st January 2021) - Dunn, David; Price, Huw; Vudriko, Tobias; Kityo, Cissy; Musoro, Godfrey; Hakim, James; Gilks, Charles; Kaleebu, Pontiano; Pillay, Deenan; Gilson, Richard
Abstract : Background: WHO treatment guidelines recommend tenofovir plus lamivudine or emtricitabine as the nucleoside reverse transcriptase inhibitor backbone in first-line regimens for HIV-infected adults. Lamivudine alone is not recommended, because of the risk of hepatitis B virus (HBV) resistance. We studied HBV responses in a large cohort of co-infected patients in a resource-limited setting. Setting: Clinical centers in Uganda and Zimbabwe. Methods: DART was a randomized trial of monitoring practices in HIV-infected adults starting antiretroviral therapy. Baseline samples were tested retrospectively for HBV serological markers and HBV DNA. Longitudinal HBV DNA testing at 48 weeks and the last available sample before HBV-relevant modification of antiretroviral therapy was performed on patients with detectable HBV DNA at baseline. Results: Two hundred twenty-four hepatitis B surface antigen-positive patients were followed for up to 4.8 years. Of the drugs with anti-HBV activity, 166 were prescribed lamivudine–tenofovir and 58 lamivudine alone. Ninety-eight percent (96/98) patients with baseline HBV DNA <6 log10 IU/mL achieved viral suppression at 48 weeks (HBV DNA <48 IU/mL), regardless of regimen, compared with 50%(26/52) for HBV DNA >6 log10 IU/mL. Of the 83 patients suppressed at 48 weeks and with follow-up data, only 7(8%) experienced viral rebound (range 200–3460 IU/mL). Of the 20 patients not suppressed at 48 weeks and with follow-up data, HBV DNA levels generally declined with lamivudine–tenofovir, but increased with lamivudine alone. Alanine transaminase flares were not observed in any patient who experienced viral rebound. Conclusions: The suppressive effect of lamivudine alone was highly durable (up to 5 years) in HIV–HBV co-infected patients with baseline HBV DNA <6 log10 IU/mL. It may be feasible to develop stratified approaches using lamivudine as the only drug with anti-HBV activity. Abstract : Supplemental Digital Content is Available in the Text.